(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article provides a scientific and pedagogical analysis of the factors contributing to the effective development of professional culture among students. The essence and content of the concept of professional culture, its structural components, as well as approaches to the professional development of an individual are methodologically substantiated.